Determination of Estazolam in Plasma by High-Performance Liquid Chromatography with Solid-Phase Extraction - SUGAWARA, Kazunobu; OTANI, Koichi; OHKUBO, Tadashi; OKUYAMA, Naoyuki; MIURA, Masatomo (Analytical Sciences, 2002)
A high-performance liquid chromatography (HPLC) assay was developed for the determination of estazolam in human plasma. Estazolam and alprazolam as an internal standard were detected by ultraviolet absorbance at 240 nm. Estazolam in plasma was extracted by a rapid and simple procedure based on cyanopropyl bonded-phase extraction. Chromatographic separation was achieved with a reversed-phase C8-5 column using a mobile phase of 0.5% potassium dihydrogenphosphate(pH 4.5)-acetonitrile (70:30, v/v). The determination of estazolam was possible in the concentration range of 1.0 - 200.0 ng/mL. The mean recovery of estazolam added to plasma was 96.1 ± 1.5% with coefficients of variation of less than 5.5%. This method is applicable for accurately monitoring the plasma level of estazolam in healthy subjects participating in scientific research.